Implementasi Living Hadis-Sufism dalam Pengembangan Spiritual Anak di Pondok Pesantren Mambaul Hisan: Tinjauan Psikologi Transpersonal - Ach. Shodiqil Hafil; Zainal Muttaqin; Desty Rahmawati; Wella Ayu Apriliani; Ahmad Zaenuddin (Spiritualita, 2025)
Technological developments have an impact on several aspects of life, and education is no exception. Parents have the responsibility for children's education, especially religious education. Therefore, parents therefore, parents choose to send their children to boarding school from an early age. This research uses a descriptive qualitative approach. The research This research uses a descriptive qualitative approach. Mambaul Hisan Islamic Boarding School. Researchers must also observe, ask questions with the aim of exploring in detail related to the data obtained regarding Living Hadith-Sufism at Mambaul Hisan Islamic Boarding School Badalpandean Ngadiluwih, Kediri. Kediri. Data collection techniques are carried out by observation, interview, and documentation.This research uses the theory of Transpersonal Psychology to be a guideline for analysis. analysis guidelines. Santri apply the values of gratitude, patience, generosity, and prohibition of anger in their daily lives. anger in daily life. There are positive implications that affect on the formation of the character of students who go to school and stay at the Mambaul Hisan Islamic Boarding School. Mambaul Hisan Islamic Boarding School, namely spiritual awareness, development of skills and character, discipline, and strengthening of character. character, discipline, and mental and emotional strengthening in forming positive and constructive personalities.